Unlocking the hypolipidemic potential of bioactive peptides derived from probiotic fermented cattle, camel, goat, and sheep milk: a comprehensive investigation through in vitro,in silico, and molecular docking studies - Mudgil, Priti; Ajayi, Feyisola Fisayo; Alyafei, Aysha Saleh; Yap, Pei-Gee; Gan, Chee-Yuen; Maqsood, Sajid (Frontiers in Sustainable Food Systems, 2024)
In this study, fermented cattle milk (FCTM), fermented camel milk (FCM), fermented goat milk (FGM), and fermented sheep milk (FSM) were produced using a total of 5 probiotic bacterial strains to investigate the release of bioactive peptides with hypolipidemic potential via in vitro inhibitory activity towards pancreatic lipase (PL) during a 14-days refrigerated storage study. The PL-inhibitory activities of these fermented milks varied according to type of probiotic strains and milk types used. Overall, Pediococcus pentosaceus MF000957 (PP-957) strain showed the highest PL inhibitory activity spanning across all milk types and therefore, PP-957 derived fermented samples were analyzed for bioactive peptide (BAP) identification by LCMS-QTOF. Identified BAP were further analyzed using in silico and bioinformatics approaches for bioactivity prediction, molecular docking and drug pharmacokinetic studies. Overall, 4 peptides derived from FCTM, 1 from FCM and 2 peptides common in FGM and FSM were predicted as active PL inhibitors based on their binding energy and number of binding sites on PL enzyme. All peptides were non-toxic, non-carcinogenic and had appropriate drug-like properties. The outcomes of this study suggest that fermented milk derived peptides from animal milks are anticipated to be useful for combating hypercholesterolemia.